A CARTOGRAPHY THAN CAN DANCE - Cazetta, Valeria [UNESP]; Hoepers Preve, Ana Maria (Univ Estadual Campinas, Fac Educacao, 2016)
Two ongoing research: What can cartography and geography do: research and inventions in education and Geographies in bodies. In both, cartography is at stake. On the one hand, cartography as a quality to go hand in hand with processes in order to allow us to say what is needed to be said; on the other, the cartography of geography that anchors the production of maps to the equivalence of space and its representation. As a result of our meeting and the meeting of two corpus of research we developed a workshop offered to Education Graduate students of Center of Humanities and Education (FAED) at the State University of Santa Catarina (UDESC). In order to make our ideas of cartography emerge we mapped the classroom where the meeting took place. We moved the cartography concepts in question, as in a dance, to promote students dislocate them, swinging between one and another. What can the cartography of a classroom do? Thus we put ourselves into action to provide means of expression of an idea, creating gaps in and through their bodies, detached from figurative and representational asphyxiating contexts of cartesian cartography. We provided various materials to them, paying attention to the maps 'constitution, therefore, what is a classroom?; what are its plans? The difficulties encountered to begin mapping, not only the way of bringing out that classroom's cartography, but how to make them present began to appear.
Keywords: Geographic education; Workshop; Geographic cartography; Guattarian/deleuzian cartography